PHYSIC QUALITY OF THE GRAIN IN HIGH QUALITY PROTEIN MAIZE POPULATIONS AND THEIR CROSSES - Oliveira, Jaison Pereira de (2007)
This study evaluated open pollinated populations of high quality protein maize (QPM) and their crosses for weight of grains, grain density, and coloration, determining the heterosis and its components as subsidy for the improvement of these populations. The analyses were carried out on 96 hybrids, derived from eight populations of dent grains and thirteen of flint grains, including their parents in a partial diallel intergroup design. A chromatic scale used for classification of egg yolks was adapted to determine grain colorations. The coefficients of variation for the three variables were small, being 3.41% for the density, 6.23% for weight of 100 grains, and 7.03% for grain coloration. Except for specific heterosis of the real density, all effects analyzed were significant. The real density means of dent and flint groups were 1.27g mL-1 and 1.16g mL-1, with average heterosis of 3.53%. The parents CMS 474 (29.92 g) and CMS 471 (34.28 g) outstood for grain weight with larger means and heterosis of 3.61%. For grain coloration, the mean of flint group was 11.77 points and of the dent group 10.53 points, with average heterosis of 3.84%. Parents ZQP 101 and ZQP 103 are recommended for the formation of a composite of dent grains, and the genotypes CMS 458, CMS 472, CMS 453 and BR 473 as parental populations in the formation of a composite of flint grains. KEY-WORDS: Zea mays; grain density; grain weight; grain coloration.